2021
DOI: 10.1103/physrevlett.126.210504
|View full text |Cite
|
Sign up to set email alerts
|

Qutrit Randomized Benchmarking

Abstract: Ternary quantum processors offer significant potential computational advantages over conventional qubit technologies, leveraging the encoding and processing of quantum information in qutrits (three-level systems). To evaluate and compare the performance of such emerging quantum hardware it is essential to have robust benchmarking methods suitable for a higher-dimensional Hilbert space. We demonstrate extensions of industry standard randomized benchmarking (RB) protocols, developed and used extensively for qubi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…We start by detailing the basic design and operation of superconducting qubits containing one or more tunnel junctions embedded within reactive circuit elements. 31 Many of these circuits have several quantum energy levels in a nonlinear potential and can, in general, function as qudits with three 32,33 or more logical states, but we will focus on a simple qubit description to frame our discussion of materials optimization. At low excitation power in the zero-voltage or 'superconducting' state, the tunnel junction is characterized by…”
Section: [H1] Conventional Josephson Tunnel Junction Qubitsmentioning
confidence: 99%
“…We start by detailing the basic design and operation of superconducting qubits containing one or more tunnel junctions embedded within reactive circuit elements. 31 Many of these circuits have several quantum energy levels in a nonlinear potential and can, in general, function as qudits with three 32,33 or more logical states, but we will focus on a simple qubit description to frame our discussion of materials optimization. At low excitation power in the zero-voltage or 'superconducting' state, the tunnel junction is characterized by…”
Section: [H1] Conventional Josephson Tunnel Junction Qubitsmentioning
confidence: 99%
“…Although, the representation of qudits with arbitrary dimension into elementary qubits is computationally efficient, even small improvements in hardware requirements can be of great practical importance in the era of noisy intermediate-scale quantum (NISQ) devices [26]. In addition, there is an increased interest in employing qudit systems as quantum information platforms [27], and there has been great experimental progress in realizing quantum information processing with qudits such as photons [28], ions [29], superconducting circuits [30], nuclear magnetic resonance platforms [31], as well as Rydberg atoms [24,32].…”
Section: Introductionmentioning
confidence: 99%
“…It has been experimentally demonstrated that the higher excited states of a transmon are almost as well controllable and measurable as the ones in the qubit subspace [23][24][25][26][27][28]. With the higher levels included, coupled transmons naturally realize the attractive Bose-Hubbard model [3,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%